The Dynamism of Cyberloafing in Digital World - Kaur, Rupinder Bir (Gyan Management Journal, 2017)
Internet is undoubtedly a necessity and its dependency is increasing every day in digital era. It has become a vital tool for communication and information sharing. Be it an employee, a student or any other individual in the organizations, the advantages of internet are manifold. The computer intervened communication has revolutionized the work environment since many decades now. However the distraction of internet users in work settings is also gaining concern. The use of internet for Non-work related activities has raised various concerns especially for organizations and educational institutions. Different researchers have given varied terms to this process of deviance such as non-work-related computing (NWRC), Cyberslacking, internet deviance, Cyber deviance, internet abuse, internet addiction etc. Cyberloafing is the technical term given to any voluntary activity of using web access and engaging in non-work related activities on a regular basis at the place of work. Cyberloafing is generally conceptualized as a form of workplace production deviance because these activities are conducted during work time and leads to unproductive use of time and distract employees from completing their work demands. Earlier studies have suggested that Cyberloafing is very prevalent and is definitely a cause of concern. The present paper discusses the literature review on the dynamics of Cyberloafing and its prevalence in organizations in the present digital era. The paper attempts to different cyber loafing behaviors and activities prevalent in the organizations in this digital era.